A highly permeable graphene oxide membrane with fast and selective transport nanochannels for efficient carbon capture. Issue 10 (19th September 2016) - Wang, Shaofei; Wu, Yingzhen; Zhang, Ning; He, Guangwei; Xin, Qingping; Wu, Xingyu; Wu, Hong; Cao, Xingzhong; Guiver, Michael D.; Jiang, Zhongyi
Abstract : Tailored physicochemical microenvironments in stacked graphene oxide nanochannels give membranes with fast and highly selective CO2 transport. Abstract : Ultrathin graphene oxide membranes using borate as both crosslinker of GO nanosheets and facilitated transport carrier of CO2 are designed and fabricated. The membranes exhibited high CO2 permeance up to 650 GPU and a CO2 /CH4 selectivity of 75, due to the rational manipulation of the interlayer nanochannel size, sufficient facilitated transport carriers and high water content.